Monitoring dan Data Logger Panel Distribusi Dengan Power Meter dan SCADA LabVIEW - Susilo, Joko Tri; Sutarmin, Sutarmin (EPIC Journal of Electrical Power Instrumentation and Control, 2024)
The use of electrical energy from year to year will increase in accordance with the progress of human civilization. With the large use of electrical energy, it is necessary to regulate and limit the use of electrical energy. Measurement of electrical quantities is usually carried out using simple measuring instruments with manual recording so that the data obtained is not real time and requires a process to obtain measurement results. Has made Distribution panel monitoring and data loggers have been created using power meters and SCADA LabVIEW. This tool helps monitor the amount of electricity in the distribution panel in real time. This research aims to create a set of distribution panel monitoring and data logger systems using a power meter and LabVIEW SCADA and find out the value of electricity on the distribution panel in real time. Making monitoring tools using LabVIEW Power Meter and SCADA as an interface, data processing and also a data system logger. In voltage testing this system can work well with an average voltage reading error of 0.03%, in current reading testing this system can work well with an average reading error of 0.3%, in active power reading testing an average error value is obtained of 0.16%, in the reactive power reading test the average error value was 2.35%, in the frequency reading test the average reading error was 0.03%, in the kWh value reading test between the LCDpower meter display and LabView the average reading error was 0.46% and the average reading error was 0.16%. The average delay in Power Meter readings to LabVIEW is 12 milliseconds.